Analysis Impact Knowledge Of Blockchain Towards Fraud Detection Skill Throught Readiness Technology As Intervening Variable - Rizky Ananda; Harti Budi Yanti (DINASTI RESEARCH, 2024)
This study aims to analyze the impact of knowledge of Blockchain on the ability to detect fraud, with technology readiness serving as an intervening variable. The research employs a quantitative approach, gathering data from auditor. The findings indicate a positive relationship between knowledge of Blockchain and fraud detection capabilities. Moreover, the readiness of technology significantly mediates this relationship, suggesting that higher levels of technology readiness enhance the positive effects of Blockchain on fraud detection. These results highlight the importance of both technical knowledge and readiness to adopt new technologies in improving fraud detection processes.